Polyether Demulsifier Complexes for Efficient Demulsification of Water-in-Heavy Oil Emulsions - Jing Li; Xiao Xia; Jinlong Gao; Hao Chen; Jun Ma (Molecules, 2025)
In the production process of the heavy oil industry, efficiently demulsifying water-in-heavy oil (W/HO) emulsions can effectively prevent the negative effects of emulsion corrosion on equipment, increase costs, reduce oil quality, and pollute the environment. Herein, polyether demulsifier complexes (PDC) were obtained by compounding fatty alcohol nonionic polyether (FAP) with perfluoropolyether (PFPEA, [CF3O(CF2CF2O)nCF3]) through a simple physical blending method. The experimental results demonstrate that PDC exhibited outstanding demulsification performance for W/HO emulsions across varying temperatures: At 60 °C and 400 ppm dosage, PDC achieved complete dehydration (100%) within just 2 min, showing significantly faster demulsification kinetics compared to FAP and PFPEA. Even at the reduced temperature of 40 °C, PDC maintained effective demulsification capability, achieving complete phase separation within 6 min. These findings collectively establish PDC’s superior demulsification efficiency for W/HO emulsions, with particularly remarkable performance under challenging low-temperature conditions. Research on the demulsification mechanism indicates that PDC achieves efficient demulsification performance due to the synergistic effect the synergistic effect of FAP and PFPEA to effectively destroy the non-covalent bonds (hydrogen and π–π stacking) of interfacially active asphaltenes (IAA) at the oil–water interface, thereby achieving demulsification of W/HO emulsion. PDC with outstanding demulsification ability exhibits significant potential for practical applications in heavy crude oil–water emulsion treatment, and this work can provide insights for developing new composite demulsifiers for petroleum production.